2019
DOI: 10.1016/j.jjcc.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of calciprotein particles measured by a new method with coronary artery plaque in patients with coronary artery disease: A cross-sectional study

Abstract: Background: Calciprotein particles (CPPs) have been suggested to be associated with the degree of coronary atherosclerosis, and have also been established as a molecular marker for clinical outcome in patients with chronic kidney disease (CKD). However, there are several concerns with regard to conventional measurement of CPPs. We therefore developed a new CPP measurement system that can detect both smaller and lower-density CPPs. Methods: We analyzed 71 consecutive patients who underwent percutaneous coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
1
23
0
3
Order By: Relevance
“…Regardless of these limitations -and given the dismal outcomes of patients on dialysis -there does appear to be a signal that is worth pursuing in future studies. Taken together with other recent studies which showed that plasma CPP levels correlated with coronary artery plaque volume and lipid content [12], these data support the idea that measurement of CPP may hold predictive value for atherosclerotic events in CKD, but this will need to be demonstrated empirically.…”
supporting
confidence: 81%
“…Regardless of these limitations -and given the dismal outcomes of patients on dialysis -there does appear to be a signal that is worth pursuing in future studies. Taken together with other recent studies which showed that plasma CPP levels correlated with coronary artery plaque volume and lipid content [12], these data support the idea that measurement of CPP may hold predictive value for atherosclerotic events in CKD, but this will need to be demonstrated empirically.…”
supporting
confidence: 81%
“…Patients with ESRD had elevated risk of all-cause and cardiovascular death, myocardial infarction, and peripheral artery disease in the case of enhanced formation of CPBs [9,10,11,12]. Augmented serum propensity to produce CPBs correlated with severe coronary artery calcification and its progression in patients with CKD stages 2 to 4 [50]; this was partially verified by a recent study showing that higher CPB serum levels are more frequently observed in patients with acute coronary syndrome as compared to those with stable angina (without pre-dialysis CKD or ESRD) and is associated with the total and lipid plaque volume [15]. Hence, serum CPB concentration might be considered as a surrogate marker of coronary atherosclerosis and coronary artery calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clinical investigations in this field having been primarily focused on kidney transplant recipients [9,10,11] and patients with end-stage renal disease [12] or pre-dialysis chronic kidney disease (CKD) [13], an elevated serum propensity to form CPBs was also observed in non-CKD patients with arterial hypertension, a major risk factor of coronary artery disease, in comparison with healthy blood donors [14]. Further, an increased CPB count in the serum is associated with the progression of stable angina to acute coronary syndrome and also with the lipid and total plaque volume in patients without detectable CKD [15]. Our unpublished data also indicated that serum levels of CPBs are higher in patients with coronary artery disease requiring bypass surgery than in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Последние ис-следования также демонстрируют, что повышенная склонность сыворотки к формированию КФБ ассоциирована с более выраженным коронарным кальцинозом и более высоким риском прогрессирования этого патологического процесса у пациентов с ХПН на различных стадиях, исключая начальную и терминальную [10]. Это косвенно подтверждается данными о том, что высокое содержание КФБ в системном кровотоке может служить суррогатным маркером КоА, коррелируя как с объемом бляшки в целом, так и с объемом ее липидного компонента, а также превалируя у пациентов с острым коронарным синдромом в сравнении с субъектами со стабильной стенокардией [14]. Полученные результаты позволяют выдвинуть гипотезу о том, что причиной увеличенной склонности крови пациентов с КаА и ИМ к формированию КФБ является снижение (до "низкого нормального" уровня) сывороточной концентрации общего белка и альбумина, роль которых в поддержании минерального гомеостаза заключается в связывании свободных ионов кальция.…”
Section: Discussionunclassified